Modelling for Causal Interrelationships by DEMATEL - Siti Aissah, Mad Ali; Sorooshian, Shahryar; Cheng, Jack Kie (Hikari Ltd, 2016)

(untitled)
This paper aims to propose researchers and professionals to employ DEMATEL as an essential element in their decision making process. Effort is taken to make it apparent that DEMATEL would be the most suitable tool when there is composite and complex mixture of aspects or factors relationship that has to be understood prior making any decision. The interdependencies could be well understood by having the Impact Relation Map chalked out via DEMATEL. This visualization with the calculations that shows the degree of impact would very well furnish decision makers with aiding information. In this paper, DEMATEL’s capability and method will be detailed out for general understanding and guidance.